2018
DOI: 10.1155/2018/9153496
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for Adult Medulloblastoma: Evaluation of Helical Tomotherapy, Volumetric Intensity Modulated Arc Therapy, and Three-Dimensional Conformal Radiotherapy and the Results of Helical Tomotherapy Therapy

Abstract: Introduction All adult medulloblastoma (AMB) patients should be treated with craniospinal irradiation (CSI) postoperatively. Because of the long irradiation range, multiple radiation fields must be designed for conventional radiotherapy technology. CSI can be completed in only one session with helical tomotherapy (HT). We evaluated the dose of HT, volumetric intensity modulated arc therapy (VMAT), and three-dimensional conformal radiotherapy (3D-CRT) of AMB and the results of 5 cases of AMB treated with HT. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Through the megavolt images obtained from each treatment, tumor dose distribution and tumor during treatment can be observed. The treatment plan can be changed, and the target volume can be adjusted in a timely fashion [21]. The ability to treat different target areas, from the stereotactic treatment of small tumors to systemic treatment, is performed by a single spiral beam.…”
Section: Introductionmentioning
confidence: 99%
“…Through the megavolt images obtained from each treatment, tumor dose distribution and tumor during treatment can be observed. The treatment plan can be changed, and the target volume can be adjusted in a timely fashion [21]. The ability to treat different target areas, from the stereotactic treatment of small tumors to systemic treatment, is performed by a single spiral beam.…”
Section: Introductionmentioning
confidence: 99%
“…On the technical side, field junctions have been necessary to achieve the required vertical radiation field extension, posing dosimetric challenges. However, the use of modern irradiation techniques, such as intensity-modulated radiotherapy (IMRT), helical treatment delivery and proton therapy, has helped overcome some of the obstacles 21,2629…”
Section: Introductionmentioning
confidence: 99%
“…However, our study found that 2 out of 36 patients with medulloblastoma developed frontal lobe metastasis, which was considered as a possible failure of the sieve plate area. With the progress of radiotherapy technology, especially the development of VMAT and TOMO program for the treatment of whole brain and spinal cord technology [11,12], the dose distribution in the target region was more uniform than that of 3DCRT and IMRT.…”
Section: Discussionmentioning
confidence: 99%